Hak Politik Kaum Minoritas Towani Tolotang di Sulawesi Selatan - Zuly Qodir (Universitas Islam Indonesia, 2014)
This article will give a description of the ethnographical border and political top minoritycitizens Group located in South Sulawesi, i.e. the believers Towani Tolotang that until now stillesksis there even in the national political scene, contemporary Towani Tolotang ghosts becauseit has representatives in the legislature. The community seems to be playing politics TowaniTolotang accommodating and make use of what was to become the will of the political regimeof Muslims and Hindus, where both of them are scrambling for mutual acknowledge and enterin the tradition of the religion: Islam or Hinduism. As citizens, communities have a variety ofstrategies Towani Tolotang which makes it able to survive and fight in the throes of variouskinds of interest; as economic and political gain, as well as the commodification of ethnicity andreligion were rampant in the area due to redistricting (decentralization). This article is based onfield research and library for the past year dealing with political citizens pressed for by the largenumber of discriminatory treatment.